RELATIONSHIP OF BODY MASS INDEX AND DYSLIPIDEMIA IN DIFFERENT AGE GROUPS OF MALE AND FEMALE POPULATION OF PESHAWAR - Humayun, Anjum; Shah, Arbab Sher; Alam, Shamim; Hussein, Hamid (Journal of Ayub Medical College Abbottabad, 2009)
Background: BMI is linearly related to the total cholesterol, LDL cholesterol and triglyceride concentrations and is, however, inversely related with HDL cholesterol, Dyslipidaemia has been recognized to be strongly associated with overweight and obesity and its comorbid conditions. Overweight and obesity is conveniently determined from body mass index (BMI). Present study was conducted in Khyber Medical College, Peshawar to investigate the importance of age in relation to BMI with dyslipidaemia. Methods: The study was conducted in Khyber Medical College Peshawar during a span of period covering from 2008 to 2009. A total of 500 volunteer male and female subjects were included, which were grouped according to age. Lipid profile was obtained against BMI of the subjects, categorized as normal, overweight and obese in different age groups. Results: The prevalence of dyslipidaemia was both age and gender dependent. Dyslipidaemia show an increasing trend with age in both male and female subjects. In females, dyslipidaemia shows a gradual increase with age for all BMI categories. However, in males, the trend is different. It has been observed that the percentage of females having dyslipidaemia was less as compared to males in the age between 20 and 59 years. On the other hand, dyslipidaemia shows a dramatic increase in females above the age of 59 years. Conclusion: There is increase in dyslipidaemia trend in our subjects with increase in BMI and age. Keywords: BMI, Dyslipidaemia, HDL-C, LDL-C